Delayed diagnosis of mild mucopolysaccharidosis type IVA - Mengni Yi; Pinquan Shen; Huiwen Zhang (BMC, 2024)
Abstract Background Mucopolysaccharidosis IVA (MPS IVA) is a lysosomal storage disease caused by biallelic variants in the N-acetylgalactosamine-6-sulfatase (GALNS) gene and is characterized by progressive and multi-system involvements, dominantly with skeletal deformities. A mild form of MPS IVA often presents with atypical symptoms and can go unrecognized for years. Methods The diagnosis of MPS IVA was confirmed via GALNS enzyme activity testing in leukocytes. Clinical features were collected. Molecular analysis was performed by next generation sequence and Sanger sequencing of the GALNS gene. The pathogenicity of the deep intron variant was verified by mRNA analyses. Results Thirteen patients with mild MPS IVA from six families were included. All probands first visit pediatric orthopedists and it took 5.6 years to be diagnosed after the disease onset. The most common symptoms in our series were waddling gait (85%), short neck (69%) and flat feet (62%). Radiologic findings indicated skeletal abnormalities in all patients, especially modification of the vertebral bodies (100%) and acetabular and femoral head dysplasia (100%). Five novel GALNS variants, including c.121-2_121-1insTTTGCTGGCATATGCA, E2 deletion, c.569 A > G, c.898 + 2 T > A, and c.1139 + 2 T > C, were identified. The most common variant, a deep intron variant NM_000512.5: c.121-210 C > T (NM_001323544.2: c.129 C > T, p.G43G), was revealed to result in an 11 bp deletion (c.128_138delGCGATGCTGAG, p.Gly43Aspfs*5) on GALNS mRNA in the GALNS transcript of NM_001323544.2. Conclusions This study provides significant insights into the clinical features and molecular characteristics that contribute to the early diagnosis of mild MPS IVA. On the basis of our cohort, orthopedists need to be able to recognize signs and symptoms of mild MPS IVA as well as the molecular and biochemical diagnosis so that an early diagnosis and treatment can be instituted.